Studi Literatur Penggunaan Frasa Instruksional Guru dalam Pembelajaran Bilingual Siswa Sekolah Dasar - Oktavia, Adella Dewi; Rokhim, An Najmun Nuri; Abidah, Wulan Nur; Wardani, Irsya Naufa Ramadhina; Andriyani, Rossa; Novita, Catrin Erma; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bilingual education in Elementary Schools equips teachers to effectively use instructions in two phrases so that students can understand the subject matter. Instructional phrases include various forms of teacher instructions used to provide guidance, explain materials, encourage participation in activities, and teach lessons. The purpose of this study is to explain the use of teacher instructional phrases in bilingual education, including their forms, functions, and strategies to improve student understanding. This study uses a literature study method (library research), by collecting and analyzing related sources such as journal articles, academic books, and research papers that discuss bilingual education and pedagogical language. The findings of the study indicate that teachers use various strategies, such as code switching, translation, and communication techniques, to deliver instructions effectively. The use of varied and contextual instructional phrases can improve student understanding and engagement in bilingual education. This study contributes to the development of bilingual education practices that are more responsive to students' linguistic needs in elementary schools and can also serve as a guide for teachers in improving their teaching proficiency.